DESAIN DIDAKTIS MATERI PELUANG BERDASARKAN LEARNING OBSTACLE PADA PEMBELAJARAN MATEMATIKA SISWA MTS - Mia Sukmawati Nur (UJMES (Uninus Journal of Mathematics Education and Science), 2021)
The background of this research was students’ learning obstacle on probability material. Didactical design research methodwas used solve this problem. The purpose of this research were looking for learning obstacle students on probabilitymaterial, didactical design based on learning obstacle on probability material, and implementation of didactical design onprobability learning .The participants of this research were VII A and VIII A class in junior high school at Ciamis.Sample were given data collection through test, interview, and documentation. Data analysis techniques with datareduction, data display, and conclusion. Based the result can be concluded: (1) the focus of obstacle epistemological learningobstacle. Were three learning obstacle, were as a) determine point of sample and space of sample, b) determine thetheoretical probability of an event, and c) determine empirical probability or relative frequency to solve real problems; (2)Created three types of didactical design based on students’ learning obstacle in workshett there (3) based on result ofdidactical design implementation most of the students’ resppons are in accordance with the predictions that have been madebefore.